High Isotropic Resolution T2 Mapping of the Lumbosacral Plexus with T2-Prepared 3D Turbo Spin Echo - Sollmann, Nico (Clin Neuroradiol, 2018)
PURPOSE: Isotropic high-resolution three-dimensional (3D) magnetic resonance neurography (MRN) is increasingly used to depict even small and highly oblique nerves of the lumbosacral plexus (LSP). The present study introduces a T2 mapping sequence (T2-prepared 3D turbo spin echo) that is B1-insensitive and enables quantitative assessment of LSP nerves. METHODS: In this study 15 healthy subjects (mean age 28.5 ± 3.8 years) underwent 3 T MRN of the LSP area three times. The T2 values were calculated offline on a voxel-by-voxel basis and measured at three segments (preganglionic, ganglionic, postganglionic) of three LSP nerves (S1, L5, L4) by two independent investigators (experienced and novice). Normative data for the different nerves were extracted and intraclass correlation coefficients (ICCs) were calculated to assess reproducibility and interobserver reliability of T2 measurements. RESULTS: The T2 mapping showed excellent reproducibility with ICCs ranging between 0.99 (S1 preganglionic) and 0.89 (L5 postganglionic). Interobserver reliability was less robust with ICCs ranging between 0.78 (S1 preganglionic) and 0.44 (L5 postganglionic) for S1 and L5. A mean T2 value of 74.6 ± 4.7 ms was registered for preganglionic segments, 84.7 ± 4.1 ms for ganglionic and 65.4 ± 2.5 ms for postganglionic segments, respectively. There was a statistically significant variation of T2 values across the nerve (preganglionic vs ganglionic vs postganglionic) for S1, L5, and L4. CONCLUSION: Our approach enables isotropic high-resolution and B1-insensitive T2 mapping of LSP nerves with excellent reproducibility. It might reflect a robust and clinically useful method for future diagnostics of LSP pathologies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00062-017-0658-9) contains supplementary material, which is available to authorized users.